Real-Time PCR Assay to Quantify Moloney Murine Leukemia Virus in Mouse Cells - Jiwon Choi; Amaiya Murphy; Takayuki Nitta (Microorganisms, 2025)
Murine leukemia viruses (MuLVs) are retroviruses that cause various diseases in mice and have served as a model for retrovirus replication and pathogenesis. MuLVs are separated into infectious exogenous retroviruses (XRVs) and endogenous retroviruses (ERVs) that are remnants of ancient infectious XRVs. Detection of XRVs in the original host cells has some difficulties because of the high similarity in sequence between ERVs and XRVs and expression of some ERV genes. There are some techniques available for monitoring retroviral replication, but each comes with limitations in terms of labor intensity, detection range, cost, and phases after infection. This study developed a novel quantitative PCR (qPCR) method for assessing replication of Moloney MuLV (M-MuLV) in mouse cells. The method amplified the region in packaging signal and gag and distinguished exogenous M-MuLV from ERVs with mouse SC-1 cells. The qPCR system could quantify viral sequences in infected cells from 16 to 72 h post-infection, with a 3-log range of difference. This was compared with the traditional infectivity assay, focal immunofluorescence assay. In conclusion, the developed qPCR system provides a rapid, sensitive, and scalable alternative for quantifying M-MuLV infectivity, with potential for broader applications in MuLV research.